The Application of Usability Testing to Analyze the Quality of Android-Based Acupressure Smart Chair Applications - M. Khairul anam; Esi Tri Emerlada; Susi Erlinda; Tashid Tashid; Torkis Nasution (Universitas Bumigora, 2023)
A smart chair is a reflection smart chair that utilizes waste tires as an alternative to acupuncture. Smart chairs are designed for people who are phobic about acupuncture needles by replacing these needles with waste tires. Acupuncture smart chairs also make it easier for users without having to go to the acupuncture practice place. This smart chair is equipped with an application that is directly connected to android. The smart chair application is an android-based remote control where users can control the application remotely. However, this application has not been tested so it is not yet known how effective and efficient the use of the application is. Therefore, researchers would conduct testing by using the usability testing method. The usability testing method is a method carried out to measure the ease of the application that has been made. The analysis in this method used five evaluation components, namely learnability, efficiency, memorability, errors, and satisfaction. This research would make instruments based on usability testing and then distribute instruments to samples by using sampling techniques. The results of this study showed a variable learnability value was 65% while the efficiency variable got a value of 74%. In terms of memorability, its value was 59%, then the Errors variable value was 74%, and the last variable, namely satisfaction, reached a value of 74%.